Cytostatic Effect of Repeated Exposure to Simvastatin: A Mechanism for Chronic Myotoxicity Revealed by the Use of Mesodermal Progenitors Derived from Human Pluripotent Stem Cells. (6th August 2015) - Peric, Delphine; Barragan, Isabel; Giraud‐Triboult, Karine; Egesipe, Anne‐Laure; Meyniel‐Schicklin, Laurène; Cousin, Christelle; Lotteau, Vincent; Petit, Vincent; Touhami, Jawida; Battini, Jean‐Luc; Sitbon, Marc; Pinset, Christian; et al.
Abstract Statin treatment of hypercholesterolemia can lead to chronic myotoxicity which is, in most cases, alleviated by drug withdrawal. Cellular and molecular mechanisms of this adverse effect have been elusive, in particular because of the lack of in vitro models suitable for long‐term exposures. We have taken advantage of the properties of human pluripotent stem cell‐derived mesodermal precursors, that can be maintained unaltered in vitro for a long period of time, to develop a model of repeated exposures to simvastatin during more than 2 weeks. This approach unveiled major differences, both in functional and molecular terms, in response to single versus repeated‐dose exposures to simvastatin. The main functional effect of the in vitro simvastatin‐induced long‐term toxicity was a loss of proliferative capacity in the absence of concomitant cell death, revealing that cytostatic effect could be a major contributor to statin‐induced myotoxicity. Comparative analysis of molecular modifications induced by simvastatin short‐term versus prolonged exposures demonstrated powerful adaptive cell responses, as illustrated by the dramatic decrease in the number of differentially expressed genes, distinct biological pathway enrichments, and distinct patterns of nutrient transporters expressed at the cell surface. This study underlines the potential of derivatives of human pluripotent stem cells for developing new approaches in toxicology, in particular for chronic toxicity testing. Stem Cells2015;33:2936–2948